The Dual Reactivity of 5‐S/5‐O‐Phenyl‐1, 4, 2‐oxathiazoles: A Fragmentation Pathway That Affords Nitriles in the Presence of Water. Issue 22 (2nd July 2015) - Lim, Yi Wee; Hewitt, Russell J.; Burkett, Brendan A.
Abstract: The rearrangement of substituted 1, 4, 2‐oxathiazoles to nitriles in the presence of water is described. Preliminary investigations suggest that the reaction pathway proceeds via a 1, 4, 2‐oxathiazolium intermediate, followed by trapping with water and subsequent decomposition to products. Abstract : An unprecedented rearrangement of 5‐phenyl‐1, 4, 2‐oxathiazoles bearing a C5 leaving group to nitriles in the presence of water is described.